Konsep Proses Pemesinan Berkelanjutan - Gusri Akhyar Ibrahim (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Lampung, 2013)
Metal industrial machining usually strongth pressure from all sectors, ether raw material industries or user metal industries. Manufacturint process which offered to all sectors industries or companies that sustainable manufakturing consist of three main factor are efective cost, enviroment and social performance. Keywords: Sustainable, machining, social, enviroment, cost.